A simplified model to predict clogging of reactive barriers. Issue 3 (27th August 2014) - de Repentigny, Carl; Courcelles, Benoît
Abstract : A study was conducted to develop a simplified analytical model to predict the progression of a carbonate clogging front in permeable reactive barriers. Permeable reactive barriers constitute an in situ remediation technique for contaminated groundwater and are composed of reactive media (magnesium oxide in this study), whose hydraulic and chemical behaviours must be studied. Models generally used to predict their clogging are relatively complex and involve the classical advection-reaction-dispersion equation. As this equation is strongly non-linear when considering a variable porosity, a simplified model predicting the loss of hydraulic conductivity would allow an easier estimation of their longevity. In this work, the generation of precipitates is predicted using chemical reactions at equilibrium. The geometry of the precipitates is estimated applying the floating sphere model, and the hydraulic behaviour is simplified to two values of permeability in the initial and the clogged states. These values were estimated using the Kozeny-Carman relation, which predicts the hydraulic conductivity of porous media considering their porosity and specific surface. Using these hypotheses, one finds that the clogging front should advance at a constant rate given constant water flow rate. Model results were successfully compared with experimental data from three one-dimensional column filtration tests to confirm this finding.